Microfinance Interventions Towards Micro and Small Enterprises Development in Pakistan and Malaysia - Muhammad Farhan, Jalil (Universiti Malaysia Sarawak (UNIMAS), 2018)
Microfinance interventions has increasingly been viewed critically to the success of micro and small businesses, with the understanding that facilitating this sector more is needed. The key objective of microfinance interventions is to keeping micro and small enterprises sustainable. However, there is little arrangement has been carried out to achieve this aim. This research investigated the effects of microfinance interventions on micro and small enterprises (MSEs) development in Pakistan and Malaysia. The study examined how microfinance with financial and"Ilon-financial microfinancing activities and features such as micro-credit, micro-savings, trainings, and business educations impact on the growth of micro and small enterprises and how it helps to start new ventures in Pakistan and Malaysia. Moreover, this study also determines the mediating relationship of social capital between micro finance interventions and micro enterprises development. In response, this study develops a model of microfinance interventions based on reviews of empirical literature to investigate through one single model. Variables were used to evolve a detailed analysis of the MSEs' development through growth and new venture creation. The model used in developing seven different hypotheses that were investigated through the survey of six hundred and sixty-nine (669) micro and small enterprises in Pakistan and Malaysia which were selected using quota sampling technique. Copies of well-structured questionnaire were distributed to sampled entrepreneurs. Furthermore, it presents and discusses empirical findings using structural equation modelling (AMOS-I8) from a survey of MSEs through their perspectives as end users of microfinance interventions. The findings revealed that microfinance interventions enhance growth of micro and small enterprises (MSEs) but also sufficient for new venture creation in Pakistan and Malaysia. The result also revealed that social capital has positively mediate the relationship among microfinance interventions and v MSEs' development. Moreover, microfinance programmes is not effective without financial and non-financial services. Financial services of microfinance are combination of credit and savings while non-financial services are based on training and business education, with all together make microfinance programmes more effectives for MSEs in Pakistan and Malaysia. This study therefore recommends a collective and cooperative micro finance strategy in the form of solidarity groups at the local level; and at the national and regional level in order to build a network of entrepreneurs groups. Furthermore, microfinance programmes should be supported with financing sources for growth ofMSEs and more funds provided for new venture creation.